PEMBUATAN SEMEN INSTAN GEOPOLIMER BERBASIS FLY ASH DENGAN SODIUM SILIKAT DARI PASIR SILIKA - M. Aditia, M. Aditia; Firdaus, Firdaus (Rang Teknik Journal, 2026)
The global construction industry faces major challenges related to sustainability and environmental impact, particularly from the use of conventional Portland cement, which emits approximately 0.8 tons of CO₂ per ton of cement produced. As an environmentally friendly alternative, geopolymers have emerged as inorganic polymeric materials formed through the reaction of aluminosilicates with alkaline activators, offering the advantage of utilizing industrial by-products such as fly ash. Fly ash, which is rich in silica (SiO₂) and alumina (Al₂O₃), has been proven to produce materials with high compressive strength, chemical resistance, and excellent thermal stability. However, geopolymerization requires sodium silicate (Na₂SiO₃), which is often costly and dependent on imports in developing countries. The local synthesis of sodium silicate from silica sand is therefore an essential solution, as previous studies have shown comparable effectiveness to commercial sodium silicate. Moreover, the development of instant geopolymer cement in the form of ready-to-use dry powder offers greater efficiency, longer shelf life, and ease of distribution. Based on these considerations, this research was conducted under the title “Development of Instant Geopolymer Cement Based on Fly Ash with Sodium Silicate from Silica Sand” to explore the potential of an environmentally friendly and practical construction material innovation.Keywords: Geopolymer Cement, Fly Ash, Sodium Silicate, Silica Sand, Sustainable Construction